IMAGES OF THE ELEMENTS IN N.A. LVOV`S WORLD ARTISTIC PICTURE - Elena N. Borowska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2022)
The purpose of this article is to identify the individual originality of Lvov in the poetic understanding of the images of the elements. The purpose stipulates the usage of methods of both contextual (in the context of the scientific and aesthetic trends of the era) and immanent (addressed to the individual creative principles and features of Lvov’s worldview) analysis of the author’s poetic texts. The article examines the artistic semantics of the images of the primary elements – fire, water, air and earth – in the poetry of N. Lvov. This problem is investigated both in relation to the dominant tendencies of the poetic embodiment of the elements in the literature of the 18th century, and with the installation to identify the individual originality of Lvov’s imagery associated with the elements of fire, water, earth and air. In the semantics and symbolism of natural elements, the dominant meanings are revealed, the frequency of the appearance in the poetic world of Lvov of representations of each of the primary elements is traced, the spectrum of its specific figurative incarnations is outlined. In particular, it was established that the element of air differs in Lvov mainly in allegorical semantics associated with the erotic sphere. In rare but expressive cases, the wind is endowed with the meaning of threat and destruction, and can also symbolize the dynamic forces of history, the fickleness of fate, the power of chaos and chance, which corresponds to the perception of the world at the end of the 18th century as a transitional cultural era characterized by an exacerbation of the feeling of instability and the rapidity of change. The semantics of fire in Lvov receives a noticeably individual sound where it is included in the number of characteristics of the Russian national character: Lvov emphasizes in it not the Nordic component, namely ardor, fervor and seething energy. In general, the specificity of the semantics of fire in Lvov is due to the fact that among the traditional connotations of this element the poet chooses mainly positively colored ones – fire almost never appears in L’vov in its catastrophic, destructive hypostasis, with the exception of the poem “On a coal fire”. The specificity of the figurative representations of the elements of the earth in L’vov differs in that in them the allegorical and literal plans coexist on equal terms, complement and reinforce each other, in general, forming the image of the earth as the embodiment of archaic, primordial power, the element in which beginnings and births are rooted, and death (mother’s womb and grave). The element of water is presented most modestly in the poetic world of Lvov (mainly in the form of a stream or pack as elements of an idyllic landscape). Water gets a brighter semantic coloring in those paintings where the poet depicts different, primarily opposite, elements in their interaction. At the same time, Lvov uses the oxymoronic combination of water and fire most often and variedly. Meeting in contexts of different genres and styles, this figurative unity is also filled with different meanings – from erotic to patriotic. As for the degree of individualization of this figurative opposition, in Lvov’s poetry it also ranges from absolute traditionalism (in “Idyll”) to completely author’s semantics (for example, in the poem “Fever”). As a result, it was concluded that the images of the primary elements in Lvov, coinciding in a number of characteristics with the tendencies of the era (allegorism, playing with contrasts), in their semantics demonstrate not only tradition, but also individual content. In particular, as the analysis shows, Lvov tends to reduce the negative meanings of the images of the elements – including the eschatological meaning widespread in his time – and to emphasize the spectrum of meanings associated with harmonious, positive principles (love, creativity, vital energy, harmony of the world order). The originality of the poet’s worldview is also reflected in the frequency ratio and combinations of the images of the elements in his poetry: fire is the most frequent and semantically diverse element here, followed by the wind, which in general imparts lightness and dynamism to Lvov`s poetic picture of the world, and the systematically repeated combination of fire and water (ice) acts as its basic opposition, which also reinforces dynamism as its leading characteristic. The work was carried out on the basis of the original poetic works of Lvov, without involving its translated and dramatic corpus of texts.